2016
DOI: 10.1128/jb.00954-15
|View full text |Cite
|
Sign up to set email alerts
|

SrrAB Modulates Staphylococcus aureus Cell Death through Regulation of cidABC Transcription

Abstract: The death and lysis of a subpopulation in Staphylococcus aureus biofilm cells are thought to benefit the surviving population by releasing extracellular DNA, a critical component of the biofilm extracellular matrix. Although the means by which S. aureus controls cell death and lysis is not understood, studies implicate the role of the cidABC and lrgAB operons in this process. Recently, disruption of the srrAB regulatory locus was found to cause increased cell death during biofilm development, likely as a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Recent studies in our laboratory have also pointed to CidB as the primary effector of cell death in this system. In these studies, we observed that the increased stationary phase cell death associated with a srrAB mutation was dependent on de‐repression of cidABC in this mutant (Windham et al ., ). Interestingly, increased cidABC expression in the srrAB mutant did not result in increased production of acetate, consistent with a role for CidA in countering CidC activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies in our laboratory have also pointed to CidB as the primary effector of cell death in this system. In these studies, we observed that the increased stationary phase cell death associated with a srrAB mutation was dependent on de‐repression of cidABC in this mutant (Windham et al ., ). Interestingly, increased cidABC expression in the srrAB mutant did not result in increased production of acetate, consistent with a role for CidA in countering CidC activity.…”
Section: Discussionmentioning
confidence: 97%
“…Double chromosomal mutations in the Δ pta and Δ ackA genetic backgrounds were generated by phi11‐mediated phage transduction. Previously, we reported the construction of Δ cidA and Δ cidB mutants (Windham et al ., ) The cidC gene was sequenced from both Δ cidA and Δ cidB mutants to confirm the absence of any polar effects that may have occurred during the gene deletion process. The cidAB mutant was constructed by amplifying the cidB deletion from KB1060 and ligating into pJB60, which contains the upstream of cidA (Windham et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…This role was predicated upon the phenotype of a cidA mutant; however, recent studies suggest that this was likely an outcome of a secondary mutation (Rice et al, 2007; Chaudhari et al, 2016). CidB, is predicted to be a membrane-associated protein, however its precise function and biochemical activity(s) are yet to be defined (Rice et al, 2003; Windham et al, 2016; Chaudhari et al, 2016). In our hands, cidA::Tn , cidB::Tn , and lrgA::Tn strains were not attenuated in fermentative biofilm formation suggesting a functional separation of the S. aureus PCD and PCL pathways, with respect to biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…While this manuscript was under preparation, a study was published investigating the influence of SrrAB upon programmed cell death mediated by cidABC [63]. The study used a special medium (TSB medium amended with 35 mM glucose) that induces cell death phenotypes [63].…”
Section: Resultsmentioning
confidence: 99%
“…The study used a special medium (TSB medium amended with 35 mM glucose) that induces cell death phenotypes [63]. The authors found that SrrAB represses the transcription of cidABC when cultured in the cell death media.…”
Section: Resultsmentioning
confidence: 99%